Marketing Mix Analysis of Banana Chips in Darma Jaya Agroindustry in Jambi City - Mayshinta, Rosa; Wahyuni, Ira; Effran, Endy; Fathoni, Zakky; Yulismi, Yulismi (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2025)
This research aims to (1) Describe the general picture of Darma Jaya Agroindustry (2) Analyze the marketing mix strategy applied by Darma Jaya Agroindustry. The analysis method used is quantitative descriptive with an assessment using a Likert scale (4,3,2,1). The number of respondents in this research was 30 consumers of Agroindustry Darma Jaya banana chips. The result of this research show that : (1) The production process activities of Agroindustry Darma Jaya are carried out by processing the main raw material in the form of horn bananas into banana chips in various flavors, with a workforce of 15 people. Production is carried out every day and the products are distributed to distributors and resellers. (2) The application of the marketing mix elements of 7P Agroindustry Darma Jaya, namely the aspects of product, price, place, people, and process, shows a good category based on the tendency of the averafe score. However, it still has aspects that fall into the less good category, namely promotion and physical evidence. Thefore, Darma Jaya Agroindustry is advised to maintain and improve the quality of aspects that are already good and make improvements to aspects that are still less than optimal, especially in terms of promotion strategies and improving physical evidence. Keywords: Marketing mix, Banana chips, Agroindustry, Likert scale